Biodiversity Exploitation for Online Entertainment - Khelifa, Rassim; Mellal, Mohammed Khalil; Mahdjoub, Hayat; Hasanah, Nur; Kremen, Claire (Frontiers in Conservation Science, 2022)
Anthropogenic wildlife exploitation threatens biodiversity worldwide. With the emergence of online trading which facilitates the physical movement of wildlife across countries and continents, wildlife conservation is more challenging than ever. One form of wildlife exploitation involves no physical movement of organisms, presenting new challenges. It consists of hunting and fishing ‘experiments’ for monetized online entertainment. Here we analyze >200 online videos of these so-called experiments in the world’s largest video platform (YouTube). These videos generated about half a billion views between 2019 and 2020. The number of target species (including threatened animals), videos, and views increased rapidly during this period. The material used in these experiments raises serious ethical questions about animal welfare and the normalisation of violence to animals on the Internet. The emergence of this phenomenon highlights the need for online restriction of this type of content to limit the spread of animal cruelty and the damage to global biodiversity. It also sheds light on some conservation gaps in the virtual sphere of the Internet which offers biodiversity-related business models that has the potential to spread globally.